Positive Compact Operators on Quaternionic Hilbert Spaces: Massoumeh Fashandi - Team, Support (Thai Journal of Mathematics, 2017)
In this paper‎, ‎ some properties of compact operators on quaternionic Hilbert spaces are studied. ‎It is shown that the positiveness of a compact normal operator on a quaternionic Hilbert space is equivalent to positiveness of its eigenvalues‎. ‎Also‎, ‎ some results analogous to compact operators on Hilbert spaces‎ are proved ‎in the quaternionic context‎.